Targeting Pathogenic Postischemic Self-Recognition by Natural IgM to Protect Against Posttransplantation Cardiac Reperfusion Injury. Issue 13 (31st March 2015) - Atkinson, Carl; Qiao, Fei; Yang, Xiaofeng; Zhu, Peng; Reaves, Nicholas; Kulik, Liudmila; Goddard, Martin; Holers, V. Michael; Tomlinson, Stephen
<x xml:space="preserve">Abstract</x> Background— Natural IgM antibodies represent a class of innate pattern recognition receptors that recognize danger-associated molecular patterns expressed on stressed or dying cells. They play important roles in tissue homeostasis by disposing of prenecrotic cells and suppressing inflammation. However, ischemic insult leads to a pathogenic level of IgM binding and complement activation, resulting in inflammation and injury. We investigate the role of self-reactive IgM in the unique setting of transplantation where the donor organ undergoes both cold and warm ischemia and global ischemic insult. Methods and Results— By transplanting hearts from wild-type donor mice into antibody-deficient mice reconstituted with specific self-reactive IgM monoclonal antibodies, we identified neoepitopes expressed after transplantation and demonstrated a key role for IgM recognition of these epitopes in graft injury. With this information, we developed and characterized a therapeutic strategy that exploited the postischemia recognition system of natural antibodies. On the basis of neoepitope identification, we constructed an anti–annexin IV single-chain antibody (scFv) and an scFv linked to Crry, an inhibitor of C3 activation (scFv-Crry). In an allograft transplantation model in which recipients contain a full natural antibody repertoire, both constructs blocked graft IgM binding and complement activation and significantly reduced graft inflammation and injury. Furthermore, scFv-Crry specifically targeted to the transplanted heart and, unlike complement deficiency, did not affect immunity to infection, an important consideration for immunosuppressed transplant recipients. Conclusions— We identified pathophysiologically important epitopes expressed within the heart after transplantation and described a novel translatable strategy for targeted complement inhibition that has several advantages over currently available approaches.